2021
DOI: 10.21037/tcr-21-1482
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted minimally invasive esophagectomy versus video-assisted minimally invasive esophagectomy: a systematic review and meta-analysis

Abstract: Background Robot-assisted minimally invasive esophagectomy (RAMIE) has been demonstrated to offer realistic three-dimensional visual clarity, flexible movement and so on. The high cost is the main reason hampering universal application. The aim of this study was to compare the short-term outcomes of RAMIE versus video-assisted minimally invasive esophagectomy (VAMIE). Methods The PubMed, EMBASE and Web of Science databases were systematically searched up to June 1, 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The RAMIE, ROBOT-2, and REVATE trials will enlighten this discussion in the future [ 21 , 25 , 26 ]. Hence, the enhanced view during abdominal and mediastinal laparoscopic, thoracoscopic, or robotic lymphadenectomy and the meticulous dissection regarding the primary tumor and the fields of lymphadenectomy have the potential to increase the number of resected lymph nodes, as clearly shown in previously published studies [ 27 , 28 , 30 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The RAMIE, ROBOT-2, and REVATE trials will enlighten this discussion in the future [ 21 , 25 , 26 ]. Hence, the enhanced view during abdominal and mediastinal laparoscopic, thoracoscopic, or robotic lymphadenectomy and the meticulous dissection regarding the primary tumor and the fields of lymphadenectomy have the potential to increase the number of resected lymph nodes, as clearly shown in previously published studies [ 27 , 28 , 30 ].…”
Section: Discussionmentioning
confidence: 96%
“…Such a retrospective American analysis compared 100 RAMIE cases with 625 MIE cases, finding no substantial differences in the short-term postoperative period [ 29 ]. Similarly, 19 retrospective studies were discussed in a systematic review and meta-analysis in 2021, and again, apart from the higher number of resected lymph nodes, MIE and RAMIE presented equal perioperative results [ 30 ].…”
Section: Cohort Studies Of Mie and Ramiementioning
confidence: 99%
“…Furthermore, a meta-analysis collected the results of eight case-control studies and resulted in similar results between MIE and RAMIE [17] . In the past, other non-randomised studies have also shown no clearly significant superiority of RAMIE over MIE; however, a trend towards more radical lymph node dissections in RAMIE patients has been reported [18][19][20] .…”
Section: Pastmentioning
confidence: 99%
“…We summarized differences in the operative and postoperative outcomes between RAMIE and MIE or OE in Tables 2 and 3. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Concerning this issue, we found 12 meta-analyses and 2 RCTs. In many studies, operation time was longer in RAMIE than in OE or MIE.…”
Section: Operative and Postoperative Outcomesmentioning
confidence: 99%
“…As oncologic variables, several authors compared the R0 resection rate and the number of lymph nodes harvested. Concerning the oncologic comparisons, we collected 10 meta-analyses [11][12][13][14]16,[18][19][20][21][22] and 2 RCTs (Table 4). 23,24) Two meta-analyses demonstrated better R0 resection rates in RAMIE compared to conventional MIE.…”
Section: Oncologic Outcomesmentioning
confidence: 99%